2021
DOI: 10.1111/ppl.13543
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances on the roles of flavonoids as plant protective molecules after UV and high light exposure

Abstract: Flavonoids are plant specialized metabolites that consist of one oxygenated and two aromatic rings. Different flavonoids are grouped according to the oxidation degree of the carbon rings; they can later be modified by glycosylations, hydroxylations, acylations, methylations, or prenylations. These modifications generate a wide collection of different molecules which have various functions in plants. All flavonoids absorb in the UV wavelengths, they mostly accumulate in the epidermis of plant cells and their bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(95 citation statements)
references
References 111 publications
4
79
0
Order By: Relevance
“…UV‐B treatment leads to the formation of free radicals in plants and the reactive ocygen species (ROS) scavenging activity of UV‐B phytoprotectants is one of the mechanisms for countering this (Ferreyra et al, 2021). Several studies have observed the higher ROS scavenging activity of dihydroxy B‐ring flavonoids such as Q 3‐ O and luteolin 7‐ O ‐glycosides compared with that of the monohydroxy B‐ones such as K 3‐ O ‐glycoides and apigenin 7‐ O ‐glycosides (Agati et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…UV‐B treatment leads to the formation of free radicals in plants and the reactive ocygen species (ROS) scavenging activity of UV‐B phytoprotectants is one of the mechanisms for countering this (Ferreyra et al, 2021). Several studies have observed the higher ROS scavenging activity of dihydroxy B‐ring flavonoids such as Q 3‐ O and luteolin 7‐ O ‐glycosides compared with that of the monohydroxy B‐ones such as K 3‐ O ‐glycoides and apigenin 7‐ O ‐glycosides (Agati et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This includes UVB perception by UVR8, transcriptional changes mediated by ELONGATED HYPOCOTYL5 (HY5), and feedback repression by REPRESSOR OF UVB PHOTOMORPHOGENESIS (RUP) ( Clayton et al , 2018 ). Evidence suggests this system also operates in mosses ( Newsham et al , 2005 ; Clarke and Robinson, 2008 ; Wolf et al , 2010 ; Waterman et al ., 2017 , 2018 ; Soriano et al , 2018 b ; C. Li et al , 2019 ; Ferreyra et al , 2021 ), although definitive data from moss mutant lines missing specific phenolic classes are lacking. The same flavonoid compounds are key for UVB-radiation tolerance in M. polymorpha and angiosperms—flavones and flavones/flavonols, respectively ( Clayton et al , 2018 ; Soriano et al , 2018 a ).…”
Section: Specialized Metabolites and Stress Tolerance In Bryophytesmentioning
confidence: 99%
“…This is particularly so for the pathways that produce ‘secondary’ or ‘specialized’ metabolites—compounds with specific functions outside the core ‘primary’ metabolic pathways common to many plant cells. These specialized metabolites, which are often stress-induced, can assist with tolerance to abiotic stresses, such as fluctuations in visible light and temperature, UVB-radiation exposure, and drought, as well as to biotic challenges from pathogens, pests, and plant competitors ( Chen et al , 2018 ; Davies et al , 2018 ; Ferreyra et al , 2021 ; Horn et al , 2021 ). Comparative genomic studies across the major groups of extant land plants—bryophytes, lycophytes, ferns, and seed plants—indicate that core components of several major specialized metabolite pathways are present across land plants but absent from extant algal relatives ( Yonekura-Sakakibara et al , 2019 ; Davies et al , 2020 ; de Vries et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Molecules 2022, 27, 4038 2 of 26 thin-layer chromatography (TLC) [3,4], ultraviolet spectroscopy (UV) [5], infrared spectroscopy (IR) [6], and nuclear magnetic resonance (NMR) [7,8]; however, the components of Chinese herbal medicine are complex and in trace amounts, and these methods cannot accurately characterize them. UV is only applicable to the determination of groups containing unsaturated bonds and aromatic structures, with low quantitative sensitivity and a small application range.…”
Section: Introductionmentioning
confidence: 99%